Pattern-Recognition Receptor Agonist-Containing Immunopotentiator CVC1302 Boosts High-Affinity Long-Lasting Humoral Immunity - Du, Luping; Hou, Liting; Yu, Xiaoming; Cheng, Haiwei; Chen, Jin; Zheng, Qisheng; Hou, Jibo (Frontiers in Immunology, 2021)
Ideally, a vaccine should provide life-long protection following a single administered dose. In our previous study, the immunopotentiator CVC1302, which contains pattern- recognition receptor (PRR) agonists, was demonstrated to prolong the lifetime of the humoral immune response induced by killed foot-and-mouth disease virus (FMDV) vaccine. To elucidate the mechanism by which CVC1302 induces long-term humoral immunity, we used 4-hydroxy-3-nitrophenylacetyl (NP)-OVA as a pattern antigen and administered it to mice along with CVC1302, emulsified together with Marcol 52 mineral oil (NP-CVC1302). From the results of NP-specific antibody levels, we found that CVC1302 could induce not only higher levels of NP-specific antibodies but also high-affinity NP-specific antibody levels. To detect the resulting NP-specific immune cells, samples were taken from the injection sites, draining lymph nodes (LNs), and bone marrow of mice injected with NP-CVC1302. The results of these experiments show that, compared with mice injected with NP alone, those injected with NP-CVC1302 had higher percentages of NP+ antigen-presenting cells (APCs) at the injection sites and draining LNs, higher percentages of follicular helper T cells (TFH), germinal center (GC) B cells, and NP+ plasma-blasts in the draining LNs, as well as higher percentages of NP+ long-lived plasma cells (LLPCs) in the bone marrow. Additionally, we observed that the inclusion of CVC1302 in the immunization prolonged the lifetime of LLPCs in the bone marrow by improving the transcription expression of anti-apoptotic transcription factors such as Mcl-1, Bcl-2, BAFF, BCMA, Bax, and IRF-4. This research provides a blueprint for designing new generations of immunopotentiators.